2020
DOI: 10.1080/11101849.2020.1761144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding ketamine to dexmedetomidine on smooth recovery from isoflurane anesthesia in adults undergoing endoscopic sinus surgery

Abstract: Background: Recovery from general anesthesia after endoscopic sinus surgery can abruptly become dangerous and having serious complications leading to lost intravenous cannulas, disconnected cables, self extubation, physical injury, increased pain and hemorrhage. This study aimed to evaluate the effects of adding ketamine to dexmedetomidine on smooth recovery from isoflurane anesthesia in adults undergoing endoscopic sinus surgery. Methods: A prospective double-blind randomized controlled study. Ten minutes bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…25,29,79 Previous research on ketamine has reported conflicting findings, 66 with some indicating that it increases the likelihood of emergence delirium 67,68,77 and others suggesting that it can reduce the likelihood. 31,32,37,50,69,[73][74][75]78,80,81 Among the studies reporting an association between ketamine and an increased likelihood of emergence delirium, they administered ketamine under both of the following conditions: 1) administered a relatively higher dose (e.g., >0.5 mg/kg); 67,77 and 2) without an additional active anesthetic agent (e.g., propofol, volatile agent) or an active sedative adjunct (e.g., dexmedetomidine). 67,77 In contrast, in the studies that reported an association between use of ketamine and a decreased likelihood of emergence delirium, they administered ketamine under one or more of the following conditions: 1) administered a relatively low dose (e.g., <0.5 mg/kg); 74,75,78,81 and/or 2) paired with an active anesthetic agent (e.g., propofol, volatile agent) and/or an active sedative adjunct (e.g., dexmedetomidine).…”
Section: Literature Review In Support Of the Medication Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…25,29,79 Previous research on ketamine has reported conflicting findings, 66 with some indicating that it increases the likelihood of emergence delirium 67,68,77 and others suggesting that it can reduce the likelihood. 31,32,37,50,69,[73][74][75]78,80,81 Among the studies reporting an association between ketamine and an increased likelihood of emergence delirium, they administered ketamine under both of the following conditions: 1) administered a relatively higher dose (e.g., >0.5 mg/kg); 67,77 and 2) without an additional active anesthetic agent (e.g., propofol, volatile agent) or an active sedative adjunct (e.g., dexmedetomidine). 67,77 In contrast, in the studies that reported an association between use of ketamine and a decreased likelihood of emergence delirium, they administered ketamine under one or more of the following conditions: 1) administered a relatively low dose (e.g., <0.5 mg/kg); 74,75,78,81 and/or 2) paired with an active anesthetic agent (e.g., propofol, volatile agent) and/or an active sedative adjunct (e.g., dexmedetomidine).…”
Section: Literature Review In Support Of the Medication Strategymentioning
confidence: 99%
“…67,77 In contrast, in the studies that reported an association between use of ketamine and a decreased likelihood of emergence delirium, they administered ketamine under one or more of the following conditions: 1) administered a relatively low dose (e.g., <0.5 mg/kg); 74,75,78,81 and/or 2) paired with an active anesthetic agent (e.g., propofol, volatile agent) and/or an active sedative adjunct (e.g., dexmedetomidine). 37,69,[73][74][75]78,80,81 For example, a double-blind study of pediatric cases with sevoflurane-based anesthesia found that patients who were administered 0.15 mg/kg of ketamine and 0.3 mcg/kg of dexmedetomidine, 10 minutes before the end of surgery, resulted in a significantly lower rate and severity of emergence delirium, relative to administration of saline (control condition). 81 Our review of literature indicates that when ketamine is administered as a low dose and/or when paired with an active anesthetic agent or sedative adjunct, there is a lower likelihood and severity of emergence delirium.…”
Section: Literature Review In Support Of the Medication Strategymentioning
confidence: 99%
“…25,29,79 Previous research on ketamine has reported conflicting findings, 66 with some indicating that it increases the likelihood of emergence delirium 67,68,77 and others suggesting that it can reduce the likelihood. 31,32,37,50,69,[73][74][75]78,80,81 Among the studies reporting an association between ketamine and an increased likelihood of emergence delirium, they administered ketamine under both of the following conditions: 1) administered a relatively higher dose (e.g., >0.5 mg/kg); 67,77 and 2) without an additional active anesthetic agent (e.g., propofol, volatile agent) or an active sedative adjunct (e.g., dexmedetomidine). 67,77 In contrast, in the studies that reported an association between use of ketamine and a decreased likelihood of emergence delirium, they administered ketamine under one or more of the following conditions: 1) administered a relatively low dose (e.g., <0.5 mg/kg); 74,75,78,81 and/or 2) paired with an active anesthetic agent (e.g., propofol, volatile agent) and/or an active sedative adjunct (e.g., dexmedetomidine).…”
Section: Midazolam (Benzodiazepine)mentioning
confidence: 99%
“…67,77 In contrast, in the studies that reported an association between use of ketamine and a decreased likelihood of emergence delirium, they administered ketamine under one or more of the following conditions: 1) administered a relatively low dose (e.g., <0.5 mg/kg); 74,75,78,81 and/or 2) paired with an active anesthetic agent (e.g., propofol, volatile agent) and/or an active sedative adjunct (e.g., dexmedetomidine). 37,69,[73][74][75]78,80,81 For example, a double-blind study of pediatric cases with sevoflurane-based anesthesia found that patients who were administered 0.15 mg/kg of ketamine and 0.3 mcg/kg of dexmedetomidine, 10 minutes before the end of surgery, resulted in a significantly lower rate and severity of emergence delirium, relative to administration of saline (control condition). 81 Our review of literature indicates that when ketamine is administered as a low dose and/or when paired with an active anesthetic agent or sedative adjunct, there is a lower likelihood and severity of emergence delirium.…”
Section: Midazolam (Benzodiazepine)mentioning
confidence: 99%
“…They observed a decrease in heart rate after dexmedetomidine administration, which returned to baseline after co-administration of ketamine (mean difference between baseline and after ketamine 6.5 bpm; 95% CI, 11.2 to 1.8; P = 0.005). In 2020, a double-blind randomized RCT concluded that adding ketamine to dexmedetomidine led to good postoperative analgesia, decreased postoperative opioid requirements, and led to smooth recovery after functional endoscopic sinus surgery [ 60 ]. Sinha et al [ 61 ] compared combination of dexmedetomidine and ketamine with dexmedetomidine alone for awake fiberoptic nasotracheal intubation and concluded that the addition of low-dose ketamine (15 mg as a bolus of 5 ml, followed by continuous infusion at 20 mg/h) further enhanced hemodynamic stability and provided better sedation than dexmedetomidine alone.…”
Section: Consensus On Ketamine Use: What Does the Evidence Say?mentioning
confidence: 99%